2016
DOI: 10.1515/bhk-2016-0022
|View full text |Cite
|
Sign up to set email alerts
|

Determination and comparison of time under tension required to perform 8, 10 and 12-RM loads in the bench press exercise

Abstract: SummaryStudy aim: To determine and compare the time under tension (TUT) required to perform 8, 10 and 12 repetition maximum (RM) loads in the bench press exercise. Material and methods: Twenty men (24.17 ± 4.69 years) were selected intentionally and properly. We included in the study physically active individuals, with a weekly frequency of physical activity of at least two days for six months, and excluded individuals with injury or pain that could interfere with the correct execution of the exercise and indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
2
8
0
2
Order By: Relevance
“…This study improved upon the methods of Lacerda et al 91 because effort was matched between conditions as every set was performed to momentary muscular failure. Thus, there is agreement in the current literature that metabolic stress increases with TUT 66 67 68 69 70 71 . Moreover, when TUT is matched, metabolic stress is greater under conditions where more repetitions are performed per set (e.g., 20 vs. 10 reps) and faster/traditional tempos (e.g., 3 vs. 6 sec) are used (91, 92).…”
Section: Applications Of Rt With High-tutsupporting
confidence: 63%
See 1 more Smart Citation
“…This study improved upon the methods of Lacerda et al 91 because effort was matched between conditions as every set was performed to momentary muscular failure. Thus, there is agreement in the current literature that metabolic stress increases with TUT 66 67 68 69 70 71 . Moreover, when TUT is matched, metabolic stress is greater under conditions where more repetitions are performed per set (e.g., 20 vs. 10 reps) and faster/traditional tempos (e.g., 3 vs. 6 sec) are used (91, 92).…”
Section: Applications Of Rt With High-tutsupporting
confidence: 63%
“…Regardless of the exact mechanisms ( Fig. 1 ), there is evidence that lactate accumulation is associated with the activation of mitochondrial biogenesis [50–55; 61–63] and that blood lactate has a positive, linear relationship with TUT during sets of RT 66 67 68 69 70 71 . Moreover, Burd et al 72 reported that higher-TUT RT (i.e., 30% 1-RM) resulted in greater sarcoplasmic protein synthesis (e.g., which includes mitochondrial proteins) compared to lower-TUT RT (i.e., 90% 1-RM).…”
Section: Upregulating Pgc-1α: the Potential Role Of Lactatementioning
confidence: 99%
“…These results suggest that the TUT can vary both due to the number of repetitions performed in the same exercise, as well as the type of exercise. The size of the body segment can influence the displacement and, consequently, the velocity and TUT during the execution of the exercise (Silva et al, 2016). Thus, this result highlights the necessity to verify the TUT for each exercise and for each muscle group.…”
Section: Discussionmentioning
confidence: 92%
“…A relação entre o número total de repetições e o tempo em que o músculo permanece sob tensão é fator importante para o crescimento muscular (Silva et al, 2017). Da Silva et al (2016) compararam o tempo sob tensão (TST) necessário para realizar 8, 10 e 12 repetições máximas (RM) no supino e encontraram diferenças no TST entre 8 e 10 RM e entre 8 e 12 RM, mas não observaram diferenças entre 10 e 12 RM. Esses achados se contrapõem ao presente estudo, onde os resultados apontaram que independentemente da ordem de execução e da diferença no número total de repetições não foram observadas diferenças significativas no TST entre as duas condições experimentais quando comparadas ao teste de 10RM, no último exercício do protocolo.…”
Section: Discussionunclassified